Risk Factors for Development of Early Onset Post-Transplant Diabetes Mellitus (PTDM) – A Prospective Study from a Tertiary Care Centre in India - Abhishek Garg; Ashish Nandwani; Manish Jain; Pranaw Kumar Jha (Indian Journal of Kidney Diseases)
Introduction: Kidney transplantation is the best form of kidney replacement therapy. Posttransplant diabetes mellitus (PTDM) is an important complication seen in transplant recipients. The present study was done to identify the incidence and risk factors for the development of early-onset PTDM at a tertiary care center in India. Materials and Methods: This was a prospective study carried out from May 1, 2016, to April 30, 2017, at a tertiary care center and included all the adult first transplant recipients. The patients were followed up for six months after transplantation and the incidence of early PTDM was noted. The patients were divided into two groups, namely, PTDM and non-PTDM groups to identify risk factors for PTDM and to compare the outcome between the two groups. Results: This study included 66 patients. Patients developing PTDM had higher age (44.07 ± 9.69 years vs. 35.98 ± 11.17 years; P = 0.013), significantly higher prevalence of family history of diabetes (57.14% vs. 15.38%; P = 0.001), higher pretransplant fasting plasma blood glucose (93.86 ± 8.59 mg/dL vs. 86.21 ± 7.53 mg/dL; P = 0.007), and higher pretransplant glycated hemoglobin (HbA1c) level (5.2% ± 0.39% vs. 4.9% ± 0.52%; P = 0.006). We did not find any association of PTDM with obesity, gender, type of induction therapy, hepatitis C infection, cytomegalovirus infection, and mean trough tacrolimus levels. Conclusions: In our study, patients who developed PTDM were of higher age, with increased levels of fasting blood sugar and HbA1c pretransplant, had a family history of diabetes, and were likely to have received antirejection therapy.